2022
DOI: 10.1097/bpo.0000000000002102
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Postoperative Outcomes Following Operative Management of Pediatric Developmental Dysplasia of the Hip

Abstract: Individual and in-training subscription rates include print and access to the online version. Institutional rates are for print only; online subscriptions are available via Ovid. Institutions can choose to purchase a print and online subscription together for a discounted rate. Institutions that wish to purchase a print subscription, please contact Wolters

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…grouped all URM patients into one cohort. They did not stratify their analysis for sub-groups, which may explain the differences in their findings compared to our study [18].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…grouped all URM patients into one cohort. They did not stratify their analysis for sub-groups, which may explain the differences in their findings compared to our study [18].…”
Section: Discussionmentioning
confidence: 64%
“…Malyavko et al analyzed 9159 patients who underwent surgical treatment for developmental dysplasia of the hip. Following multivariate analyses, the authors found that patients from underrepresented minority (URM) groups (African American or African American, Hispanic, Native American or Alaskan, and Native Hawaiian or Pacific Islander) had an increased risk for unplanned reintubation compared to white patients [18]. Similarly, Patel et al aimed to evaluate whether race influences the healing of osteochondritis dissecans (OCD) lesions in pediatric patients [9].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, Noureldine et al reported a longer length of hospital stay, increased postoperative complications, and increased costs for Black patients compared to White patients after thyroid and parathyroid patients [19]. In that study, it was reported that African Americans had less access to intermediate and high-volume surgeons [16].…”
Section: Discussionmentioning
confidence: 95%
“…Another study found higher rates of respiratory events including laryngo/bronchospasm, pneumonia, pulmonary edema, intubation, prolonged intubation, and ventilation in Black children after tonsillectomy compared with children of other races [15]. Furthermore, Malyavko et al found that children from underrepresented minority groups had higher odds of undergoing unplanned reintubation compared with White children following surgical treatment of hip dysplasia [16].…”
Section: Discussionmentioning
confidence: 99%
“…These findings have been echoed across surgical specialties, with minority children incurring poorer outcomes. Minority children have a greater risk of postoperative pulmonary complications [ 70 73 ], cardiovascular complications, and cardiac arrest [ 70 , 73 ], surgical wound complications [ 61 ••, 73 ], unplanned reoperation [ 61 ••], and readmission [ 74 ]. Even more concerning, however, is disparate postoperative mortality rates.…”
Section: Postoperative Racial Disparitiesmentioning
confidence: 99%